Galaxy InteractoMIX: An Integrated Computational Platform for the Study of Protein-Protein Interaction Data - Mirela-Bota, Patricia; Aguirre-Plans, Joaquim; Meseguer, Alberto; Galletti, Cristiano; Segura, Joan; Planas-Iglesias, Joan; Garcia-Garcia, Javi; Guney, Emre; Oliva, Baldo; Fernandez-Fuentes, Narcis (Journal of molecular biology, 2021)
Protein interactions play a crucial role among the different functions of a cell and are central to our understanding of cellular processes both in health and disease. Here we present Galaxy InteractoMIX (http://galaxy.interactomix.com), a platform composed of 13 different computational tools each addressing specific aspects of the study of protein-protein interactions, ranging from large-scale cross-species protein-wide interactomes to atomic resolution level of protein complexes. Galaxy InteractoMIX provides an intuitive interface where users can retrieve consolidated interactomics data distributed across several databases or uncover links between diseases and genes by analyzing the interactomes underlying these diseases. The platform makes possible large-scale prediction and curation protein interactions using the conservation of motifs, interology, or presence or absence of key sequence signatures. The range of structure-based tools includes modeling and analysis of protein complexes, delineation of interfaces and the modeling of peptides acting as inhibitors of protein-protein interactions. Galaxy InteractoMIX includes a range of ready-to-use workflows to run complex analyses requiring minimal intervention by users. The potential range of applications of the platform covers different aspects of life science, biomedicine, biotechnology and drug discovery where protein associations are studied.
Keywords: Amino Acid Motifs; interactomics; uživatelské rozhraní počítače; User-Computer Interface; Galaxy platform; workflows; konzervovaná sekvence; výpočetní biologie; průběh práce; Conserved Sequence; Workflow; aminokyselinové motivy; mapování interakce mezi proteiny; Software; molekulární modely; Protein Interaction Mapping; Models, Molecular; integration; software; network analyses; Computational Biology